2013
DOI: 10.1038/nmeth.2442
|View full text |Cite
|
Sign up to set email alerts
|

A simple tool to improve pluripotent stem cell differentiation

Abstract: We develop a method to overcome previously documented restrictions on the differentiation propensities of pluripotent stem cells. Culturing pluripotent stem cells in dimethylsulfoxide (DMSO) activates the retinoblastoma protein, increases the proportion of cells in the early G1 phase of the cell cycle, and subsequently improves their competency for directed differentiation into multiple lineages in more than 25 stem cell lines. DMSO treatment also promotes terminal differentiation into functional derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
178
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(205 citation statements)
references
References 36 publications
20
178
1
Order By: Relevance
“…The yield of cardiomyocytes was, however, quite low, especially with embryoid body-based protocols that patently provided no more that several per cent of robustly beating cells. Different small-molecule approaches to increase the yield were tried and tested, and in 2013 was published a report that treatment of differentiating cells with dimethylsulfoxide (DMSO) dramatically increased the differentiation rates in all germ layer lineages, including the cardiogenic lineage [18]. Fig.…”
Section: Brief Historical Overview Of the Attempts To Cultivate Rhythmentioning
confidence: 99%
See 4 more Smart Citations
“…The yield of cardiomyocytes was, however, quite low, especially with embryoid body-based protocols that patently provided no more that several per cent of robustly beating cells. Different small-molecule approaches to increase the yield were tried and tested, and in 2013 was published a report that treatment of differentiating cells with dimethylsulfoxide (DMSO) dramatically increased the differentiation rates in all germ layer lineages, including the cardiogenic lineage [18]. Fig.…”
Section: Brief Historical Overview Of the Attempts To Cultivate Rhythmentioning
confidence: 99%
“…Treatment with 1-2 % DMSO for 24-28 h was shown to increase the yield of differentiated cells originating from all three germ layers, the cardiogenic lineage included [18]. The authors of the cited study claim that the phenomenon has been observed with > 25 different human embryonic stem cell lines and induced pluripotent stem cell lines.…”
Section: Increasing the Propensity For Differentiation Along Multiplementioning
confidence: 99%
See 3 more Smart Citations